Polymer composition, lubricating oil additive, viscosity index improver, lubricating oil composition, method for producing polymer composition, and method for producing macromonomer
By using (meth)acrylic copolymers with specific structural units in lubricating oil, the differential molecular weight distribution and scattering intensity of the polymer composition are optimized, and the problem of the viscosity of lubricating oil is reduced at high temperatures is solved, and the high viscosity index and Performance stability at low fuel efficiency.
Patent Information
- Application Number
- CN202180010370.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-25
- Filing Date
- 2021-03-25
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-03-25
AI Technical Summary
The existing lubricating oil compositions have a lower viscosity at high temperatures, which cannot effectively improve the viscosity index, and it is difficult to maintain performance under low fuel efficiency conditions.
Using (meth)acrylic copolymers containing specific structural units as polymer compositions, the differential molecular weight distribution and scattering intensity are optimized by gel permeation chromatography and small angle X-ray scattering technology to form a polymer composition with a high viscosity index. .
The viscosity index of lubricating oil is significantly improved, ensuring performance stability under low and high temperature conditions, and improving fuel efficiency and lubricating performance.
Smart Images

Figure FDA0004996012600000041 
Figure GDA0003757433320000061 
Figure GDA0003757433320000141
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer composition for use in engine oil or the like, a lubricating oil additive, a viscosity index improver, a lubricating oil composition, a method for producing the polymer composition, and a method for producing a macromonomer.
[0002] This application claims priority based on Tokugan Application No. 2020-055130 filed in Japan on March 25, 2020 and Tokugan Application No. 2020-055131 filed in Japan on March 25, 2020, the contents of which are incorporated herein by reference. Background Art
[0003] Lubricating oil compositions such as engine oils and gear oils used in automobiles and the like are required to have a certain viscosity that can protect components over a wide range from low to high temperatures.
[0004] However, conventional lubricating oil compositions have a reduced viscosity at high temperatures and cannot exhibit their original performance. In addition, in order to cope with the recent decline in fuel efficiency, it is desired to reduce the viscosity of lubricating oils in the practical temperature range and suppress the decrease in viscosity at high temperatures (improve the viscosity index).
[0005] Therefore, for example, Patent Documents 1 and 2 describe viscosity index improvers composed of a (meth)acrylate polymer having a long-chain alkyl group.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-203913
[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 10-298576 Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, the methods described in Patent Documents 1 and 2 do not provide a sufficient effect of improving the viscosity index.
[0012] The present invention aims to solve these problems.
[0013] Methods for solving problems
[0014] The gist of the present invention is a polymer composition comprising a (meth)acrylic acid-based copolymer A, wherein the (meth)acrylic acid-based copolymer A is a copolymer comprising structural units derived from a methacrylic acid alkyl ester a1 having 5 to 14 carbon atoms in the alkyl group, structural units derived from an acrylate alkyl ester a2 having 5 to 14 carbon atoms in the alkyl group, and structural units derived from an acrylate alkyl ester a3 having 1 to 4 carbon atoms in the alkyl group.
[0015] The gist of the present invention is a polymer composition, wherein the differential distribution value in the differential molecular weight distribution curve of the polymer composition measured by gel permeation chromatography satisfies the following formula 1, and the size q of the scattering vector of the small-angle X-ray scattering of a 35 wt% solution of the polymer composition in the following base oil at 25° C. is 0.07 nm -1 Above and 2nm -1 The maximum value of the normalized backscatter intensity within the range below 40 cm -1 above.
[0016] dMp30 / dMp≥0.65…1
[0017] dMp30: A differential distribution value of molecular weight corresponding to 30% of the peak top molecular weight measured by gel permeation chromatography.
[0018] ·dMp: differential distribution value of peak top molecular weight measured by gel permeation chromatography.
[0019] Base oil: API standard Group III, or Group III Plus
[0020] [1] A polymer composition,
[0021] The differential distribution value represented by the following formula 1 in the differential molecular weight distribution curve of the above-mentioned polymer composition measured by gel permeation chromatography is 0.65 or more, preferably 0.70 or more and 1.0 or less, more preferably 0.75 or more and 1.0 or less, and further preferably 0.80 or more and 1.0 or less.
[0022] The size q of the scattering vector of a 35 wt% base oil solution of the above polymer composition at 25°C small angle X-ray scattering is 0.07 nm -1 Above and 2nm -1 The maximum value of the normalized backscatter intensity within the range below 40 cm -1 More than 40cm, more preferably -1 Over 1100cm -1 Below, more preferably 60cm -1 Over 500cm -1Below, more preferably 80cm -1 Over 450cm -1 the following.
[0023] dMp30 / dMp≥0.65…1
[0024] dMp30: A differential distribution value of molecular weight corresponding to 30% of the peak top molecular weight measured by gel permeation chromatography.
[0025] ·dMp: differential distribution value of peak top molecular weight measured by gel permeation chromatography.
[0026] Base oil: API standard Group III, or Group III Plus
[0027] [2] The polymer composition according to [1],
[0028] The polymer composition is a polymer composition comprising a (meth)acrylic copolymer A.
[0029] The (meth)acrylic copolymer A is a copolymer comprising structural units derived from a methacrylate alkyl ester a1 having 5 to 14 carbon atoms in the alkyl group, structural units derived from an acrylate alkyl ester a2 having 5 to 14 carbon atoms in the alkyl group, and structural units derived from an acrylate alkyl ester a3 having 1 to 4 carbon atoms in the alkyl group.
[0030] [3] The polymer composition according to [2],
[0031] In the (meth)acrylic copolymer A, the content of the structural unit derived from the alkyl methacrylate a1 is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 45% by mass or less, and further preferably 10% by mass or more and 40% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0032] [4] A polymer composition,
[0033] It is a polymer composition comprising a (meth)acrylic copolymer A,
[0034] The (meth)acrylic copolymer A is a copolymer comprising a structural unit derived from a methacrylic acid alkyl ester a1 having an alkyl group with 5 to 14 carbon atoms, a structural unit derived from an acrylate alkyl ester a2 having an alkyl group with 5 to 14 carbon atoms, and a structural unit derived from an acrylate alkyl ester a3 having an alkyl group with 1 to 4 carbon atoms.
[0035] In the (meth)acrylic copolymer A, the content of the structural unit derived from the alkyl methacrylate a1 is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 45% by mass or less, and further preferably 10% by mass or more and 40% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0036] [5] The polymer composition according to any one of [2] to [4],
[0037] In the (meth)acrylic copolymer A, the content of the structural unit derived from the alkyl acrylate a2 is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 45% by mass or less, and further preferably 10% by mass or more and 40% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0038] [6] The polymer composition according to any one of [2] to [5],
[0039] In the (meth)acrylic copolymer A, the content of the structural unit derived from the alkyl acrylate a3 is preferably 30% by mass or more and 80% by mass or less, more preferably 35% by mass or more and 75% by mass or less, and further preferably 40% by mass or more and 70% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0040] [7] A polymer composition,
[0041] It is a polymer composition comprising a (meth)acrylic copolymer A,
[0042] The (meth)acrylic copolymer A is a copolymer comprising a structural unit derived from a methacrylic acid alkyl ester a1 having an alkyl group with 5 to 14 carbon atoms, a structural unit derived from an acrylate alkyl ester a2 having an alkyl group with 5 to 14 carbon atoms, and a structural unit derived from an acrylate alkyl ester a3 having an alkyl group with 1 to 4 carbon atoms.
[0043] In the (meth)acrylic copolymer A, the content of the structural unit derived from the alkyl acrylate a3 is preferably 30% by mass or more and 80% by mass or less, more preferably 35% by mass or more and 75% by mass or less, and further preferably 40% by mass or more and 70% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0044] [8] The polymer composition according to [7],
[0045] In the (meth)acrylic copolymer A, the content of the structural unit derived from the alkyl acrylate a2 is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 45% by mass or less, and further preferably 10% by mass or more and 40% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0046] [9] The polymer composition according to any one of [2] to [8],
[0047] The (meth)acrylic copolymer A is a copolymer including a structural unit derived from an alkoxyalkyl (meth)acrylate a4.
[0048]
[10] The polymer composition according to [9],
[0049] In the (meth)acrylic copolymer A, the content of the structural unit derived from the (meth)acrylic acid alkoxyalkyl ester a4 is preferably 1% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 25% by mass or less, and further preferably 5% by mass or more and 20% by mass or less, relative to the total mass of the (meth)acrylic copolymer A.
[0050]
[11] The polymer composition according to any one of [1] to
[10] ,
[0051] The differential distribution value represented by the following formula in the differential molecular weight distribution curve measured by gel permeation chromatography is 0.65 or more, preferably 0.70 or more and 1.0 or less, more preferably 0.75 or more and 1.0 or less, and further preferably 0.80 or more and 1.0 or less.
[0052] dMp30 / dMp≥0.65…1
[0053] dMp30: differential distribution value of the molecular weight corresponding to 30% of the peak top molecular weight.
[0054] dMp: differential distribution value of peak top molecular weight.
[0055]
[12] The polymer composition according to any one of [1] to
[11] ,
[0056] The scattering vector size of the API standard Group III or Group III Plus 35wt% base oil solution of the above polymer composition at 100°C is q==0.1nm -1 The normalized backscatter intensity at 1 cm -1 More preferably 1.5 cm -1 Over and 100.0cm -1Below, more preferably 2cm -1 Over and 50.0cm -1 the following.
[0057]
[13] The polymer composition according to any one of [1] to
[12] ,
[0058] The mass average molecular weight of the polymer composition measured by gel permeation chromatography is preferably 50,000 to 2,000,000, more preferably 100,000 to 1,500,000, and even more preferably 150,000 to 1,000,000.
[0059]
[14] The polymer composition according to any one of [1] to
[13] ,
[0060] The molecular weight distribution of the polymer composition as measured by gel permeation chromatography is preferably 5 or more and 20 or less, more preferably 6 or more and 18 or less, and even more preferably 7 or more and 15 or less.
[0061]
[15] The polymer composition according to any one of [2] to
[14] ,
[0062] The (meth)acrylic copolymer A is a graft copolymer.
[0063]
[16] The polymer composition according to
[15] ,
[0064] The graft copolymer includes a structural unit derived from the vinyl radical polymerizable monomer m1 and a structural unit derived from a macromonomer M other than the vinyl radical polymerizable monomer m1.
[0065]
[17] The polymer composition according to
[16] ,
[0066] The vinyl radical polymerizable monomer m1 is an alkyl acrylate a2 having an alkyl group with 5 to 14 carbon atoms and an alkyl acrylate a3 having an alkyl group with 1 to 4 carbon atoms.
[0067]
[18] The polymer composition according to
[16] or
[17] ,
[0068] The macromonomer M includes a structural unit derived from a vinyl radical polymerizable monomer m2.
[0069]
[19] The polymer composition according to
[18] ,
[0070] The vinyl radical polymerizable monomer m2 includes an alkyl methacrylate a1 having an alkyl group with 5 to 14 carbon atoms.
[0071]
[20] The polymer composition according to any one of
[16] to
[19] ,
[0072] The macromonomer M has a structure of Formula 2 below.
[0073] [Chemistry 1]
[0074]
[0075] (Where X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH, Y 1 ~Y n Each independently represents a substituent bonded to the vinyl group of the vinyl radical polymerizable monomer m2. Z represents a terminal group, and n represents an integer of 2 to 10,000.
[0076]
[21] The polymer composition according to any one of
[16] to
[20] ,
[0077] The number average molecular weight of the macromonomer M as measured by gel permeation chromatography is preferably 500 to 30,000, more preferably 1,000 to 25,000, and particularly preferably 2,000 to 20,000.
[0078]
[22] A lubricating oil additive,
[0079] It comprises the polymer composition described in any one of [1] to
[21] .
[0080]
[23] A viscosity index improver,
[0081] It comprises the polymer composition described in any one of [1] to
[21] .
[0082]
[24] A lubricating oil composition,
[0083] It comprises the polymer composition described in any one of [1] to
[21] .
[0084]
[25] The method for producing a polymer composition according to any one of [1] to
[21] ,
[0085] The invention relates to a method for producing a polymer composition by polymerizing a monomer mixture containing a macromonomer and a vinyl radical polymerizable monomer in a base oil.
[0086] The above-mentioned macromonomer is a macromonomer polymerized in a base oil.
[0087]
[26] The method for producing a polymer composition according to
[25] ,
[0088] α-Methylstyrene dimer was used as a chain transfer agent.
[0089]
[27] A method for producing a macromonomer,
[0090] A monomer mixture containing a vinyl radical polymerizable monomer is polymerized in a base oil using a cobalt chain transfer agent.
[0091]
[28] A lubricating oil composition,
[0092] It comprises the polymer composition described in
[20] or
[21] , and a base oil.
[0093] Effects of the Invention
[0094] According to the present invention, a polymer composition, a lubricating oil additive, a viscosity index improver, and a lubricating oil composition having a high viscosity index improving effect can be provided.
[0095] Furthermore, according to the method for producing a polymer composition of the present invention, a polymer composition having a high viscosity index improvement effect can be produced.
[0096] Furthermore, according to the method for producing a macromonomer of the present invention, it is possible to produce a macromonomer capable of producing a polymer composition having a high viscosity index-improving effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0097] Figure 1 This is a differential molecular weight distribution curve of the polymer composition of the present invention produced in Example 2. DETAILED DESCRIPTION
[0098] The differential distribution value in the differential molecular weight distribution curve of the polymer composition of the present invention measured by gel permeation chromatography (GPC) satisfies the following formula 1.
[0099] dMp30 / dMp≥0.65…1
[0100] dMp30: A differential distribution value of molecular weight corresponding to 30% of the peak top molecular weight measured by gel permeation chromatography.
[0101] dMp: differential distribution value of peak top molecular weight measured by GPC.
[0102] The polymer composition of the present invention is a mixture of polymers with different structures such as a low molecular weight diblock copolymer and a high molecular weight graft copolymer, and the above differential molecular weight distribution curve has a wider distribution and has multiple peaks or shoulders. The polymer composition of the present invention satisfies the above formula 1, thereby showing the presence of a graft copolymer that helps to improve the viscosity index. From the perspective of improving the viscosity index, the above dMp30 / dMp is more preferably 0.70 or more, and more preferably 0.75 or more. More specifically, the above dMp30 / dMp is preferably 0.70 or more and 2.0 or less, more preferably 0.75 or more and 1.5 or less, and more preferably 0.80 or more and 1.0 or less.
[0103] In the polymer composition of the present invention, the size q of the scattering vector of a 35 wt% base oil solution of the polymer composition at 25°C small angle X-ray scattering is 0.07 nm. -1 Above and 2nm -1 The maximum value of the normalized backscatter intensity within the range below 40 cm -1 More specifically, the maximum value of the standardized backscattering intensity is more preferably 40 cm -1 Over 1100cm -1 Below, more preferably 60cm -1 Over 500cm -1 Below, more preferably 80cm -1 Over 450cm -1 the following.
[0104] The magnitude q of the scattering vector of the small-angle X-ray scattering represents the inverse of the distance between particles in the base oil solution, and the scattering intensity represents the particle nature. If the maximum value of the normalized backscattering intensity of the polymer composition of the present invention is 40 cm -1 As described above, the polymer is dispersed in the base oil at 25°C in a fine particle structure, and the increase in the viscosity of the base oil at low temperatures can be suppressed.
[0105] It should be noted that the above base oil is an oil of Group III or Group III Plus base oil according to the API (American Petroleum Institute) standard. The Group III base oil is a mineral oil having a viscosity index (VI) ≥ 120, a saturated hydrocarbon content (Vol.%) ≥ 90, and a sulfur content (MASS%) ≤ 0.03, and the Group III Plus base oil is a mineral oil having a viscosity index (VI) ≥ 135, a saturated hydrocarbon content (Vol.%) ≥ 90, and a sulfur content (MASS%) ≤ 0.03.
[0106] Furthermore, in the polymer composition of the present invention, the scattering vector size q of a 35 wt% base oil solution of the polymer composition at 100° C. in small-angle X-ray scattering is 0.1 nm. -1 The normalized backscatter intensity at 1 cm -1 More preferably 1.5 cm -1 More than 10.0cm -1 Below, more preferably 2cm -1 Over and 9.0cm -1 The above normalized backscatter intensity is 1 cm -1 As described above, the polymer does not completely dissolve in the base oil even at 100°C, and a partially shrunk structure remains. Therefore, the viscosity is likely to increase even under high temperature (150°C) and high shear conditions.
[0107] In addition, from the perspective of being able to improve solubility in base oil and viscosity index, the mass average molecular weight of the above-mentioned polymer composition measured by GPC is preferably 50,000 to 2,000,000, more preferably 100,000 to 1,500,000, and further preferably 150,000 to 1,000,000.
[0108] Furthermore, from the viewpoint of achieving good solubility in base oil and viscosity index, the molecular weight distribution of the polymer composition measured by GPC is preferably 5 or more and 20 or less, more preferably 6 or more and 18 or less, and even more preferably 7 or more and 15 or less.
[0109] In addition, the said molecular weight distribution is the value calculated from the mass average molecular weight (Mw) / number average molecular weight (Mn).
[0110] In addition, the polymer composition of the present invention preferably contains a (meth)acrylic copolymer (A).
[0111] The (meth)acrylic copolymer A is a copolymer in which at least a part of the structural units are structural units derived from (meth)acrylic monomers. The (meth)acrylic copolymer A may further include structural units derived from monomers other than (meth)acrylic monomers (eg, styrene).
[0112] Examples of the (meth)acrylic monomer include (meth)acrylic acid, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxyethyl hexahydrophthalate; (meth)acrylic acid esters containing a carboxyl group, such as (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl methacrylate, n-heptyl methacrylate, n-octyl methacrylate, and (meth)acrylate. ) nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, isopentyl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, 3-isopropylheptyl (meth)acrylate, isoundecyl (meth)acrylate, 2-tert-butylheptyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isotetradecyl (meth)acrylate (meth)acrylates having an alkyl group such as (meth)acrylates such as esters; (meth)acrylates having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerol mono(meth)acrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate; (meth)acrylates having a cyclic alkyl group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and adamantyl (meth)acrylate; (meth)acrylates having a cyclic alkyl group such as (meth)acrylate; (meth)acrylates having an aromatic ring structure such as phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, (1-naphthyl)methyl (meth)acrylate; (meth)acrylates having a heterocyclic structure such as tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, and (meth)acryloylmorpholine;(Meth)acrylate methoxyethyl, (meth)acrylate ethoxyethyl, (meth)acrylate ethoxydiethylene glycol (meth)acrylate, (meth)acrylate butoxyethyl, 2-ethylhexyldiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate and other (meth)acrylate alkoxyalkyl esters; 3-(meth)acryloxypropyl trimethoxysilane, 3-(meth)acryloxypropyl triethoxysilane, 2-(meth)acryloxyethyl acid phosphate, (meth)acrylate trifluoroethyl and (meth)acrylate heptadecafluorodecyl, (meth)acrylate dimethylaminoethyl, (meth)acrylate diethylaminoethyl, (meth)acrylamide and the like. Two or more of these may be used in combination. ;
[0113] Furthermore, the (meth)acrylic copolymer A is preferably a copolymer comprising structural units derived from a methacrylate alkyl ester a1 having an alkyl group with 5 to 14 carbon atoms, structural units derived from an acrylate alkyl ester a2 having an alkyl group with 5 to 14 carbon atoms, and structural units derived from an acrylate alkyl ester a3 having an alkyl group with 1 to 4 carbon atoms.
[0114] Examples of the alkyl methacrylate a1 include methacrylates having a linear alkyl group such as n-pentyl methacrylate, n-hexyl methacrylate, n-heptyl methacrylate, n-octyl methacrylate, n-nonyl methacrylate, n-decyl methacrylate, n-undecyl methacrylate, n-dodecyl methacrylate, n-tridecyl methacrylate, and n-tetradecyl methacrylate; methacrylates having a branched alkyl group such as isopentyl methacrylate, 2-ethylhexyl methacrylate, isononyl methacrylate, isodecyl methacrylate, 3-isopropylheptyl methacrylate, isoundecyl methacrylate, 2-tert-butylheptyl methacrylate, isododecyl methacrylate, isotridecyl methacrylate, and isotetradecyl methacrylate; and methacrylates having a cyclic alkyl group such as cyclopentyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, dicyclopentenyl methacrylate, dicyclopentenyloxyethyl methacrylate, dicyclopentyl methacrylate, and adamantyl methacrylate. Two or more of these may be used in combination.
[0115] In addition, from the viewpoint of excellent effect of improving the viscosity index, a linear or branched alkyl methacrylate having 8 to 14 carbon atoms is preferred, a linear or branched alkyl methacrylate having 10 to 14 carbon atoms is more preferred, and a linear or branched alkyl methacrylate having 12 to 14 carbon atoms is further preferred.
[0116] In order to improve the solubility in the base oil and the viscosity index, the content of the structural unit derived from the alkyl methacrylate a1 is preferably 1% by mass to 50% by mass, more preferably 5% by mass to 45% by mass, and even more preferably 10% by mass to 40% by mass, relative to the total mass of the (meth)acrylic copolymer A.
[0117] In addition, in this specification, the content of a structural unit can be calculated from the input amount of the monomer which comprises each structural unit.
[0118] As the above-mentioned alkyl acrylate a2, for example, acrylates having straight-chain alkyl groups such as n-pentyl acrylate, n-hexyl acrylate, n-heptyl acrylate, n-octyl acrylate, n-nonyl acrylate, n-decyl acrylate, n-undecyl acrylate, n-dodecyl acrylate, n-tridecyl acrylate, and n-tetradecyl acrylate can be listed; acrylates having branched alkyl groups such as isopentyl acrylate, 2-ethylhexyl acrylate, isononyl acrylate, isodecyl acrylate, 3-isopropylheptyl acrylate, isoundecyl acrylate, 2-tert-butylheptyl acrylate, isododecyl acrylate, isotridecyl acrylate, and isotetradecyl acrylate; acrylates having cyclic alkyl groups such as cyclopentyl acrylate, cyclohexyl acrylate, isobornyl acrylate, dicyclopentenyl acrylate, dicyclopentenyloxyethyl acrylate, dicyclopentyl acrylate, and adamantyl acrylate can be listed. Two or more of these can also be used in combination.
[0119] It should be noted that, from the viewpoint of excellent effect of improving the viscosity index, linear or branched alkyl acrylates having 8 to 14 carbon atoms are preferred, linear or branched alkyl acrylates having 10 to 14 carbon atoms are more preferred, and linear or branched alkyl acrylates having 12 to 14 carbon atoms are further preferred.
[0120] In addition, from the viewpoint of being able to improve the solubility in the base oil and the viscosity index, the structural unit derived from the above-mentioned alkyl acrylate a2 is preferably 1 mass % to 50 mass % based on the total mass of the above-mentioned (meth)acrylic acid-based copolymer A, more preferably 5 mass % to 45 mass % and even more preferably 10 mass % to 40 mass %.
[0121] Examples of the alkyl acrylate a3 include acrylates having a linear alkyl group such as methyl acrylate, ethyl acrylate, n-propyl acrylate, and n-butyl acrylate; and acrylates having a branched alkyl group such as isopropyl acrylate, isobutyl acrylate, tert-butyl acrylate, and sec-butyl acrylate. Two or more of these may be used in combination.
[0122] In addition, from the viewpoint of excellent effect of improving the viscosity index, an alkyl acrylate having 2 to 4 carbon atoms is preferred, an alkyl acrylate having 3 to 4 carbon atoms is more preferred, and an alkyl acrylate having 4 carbon atoms is further preferred.
[0123] In addition, from the viewpoint of being able to improve the solubility in the base oil and the viscosity index, the structural unit derived from the above-mentioned alkyl acrylate a3 is preferably 30 mass % or more and 80 mass % or less, more preferably 35 mass % or more and 75 mass % or less, and further preferably 40 mass % or more and 70 mass % or less, relative to the total mass of the above-mentioned (meth)acrylic acid-based copolymer A.
[0124] Furthermore, in order to adjust the solubility and viscosity index in the base oil, the (meth)acrylic acid-based copolymer A may further include a structural unit derived from an alkoxyalkyl (meth)acrylate a4 in addition to the methacrylate alkyl ester a1, the acrylate alkyl ester a2, and the acrylate alkyl ester a3.
[0125] Examples of the (meth)acrylic acid alkoxyalkyl ester a4 include methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxyethyl (meth)acrylate, 2-ethylhexyldiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, etc. These may be used in combination of two or more.
[0126] In addition, from the viewpoint of excellent effect of improving the viscosity index, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, and butoxyethyl (meth)acrylate are preferred, methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate are more preferred, and methoxyethyl (meth)acrylate is further preferred.
[0127] In addition, from the viewpoint of being able to improve the solubility in the base oil and the viscosity index, the structural unit derived from the alkoxyalkyl (meth)acrylate a4 is preferably 1% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 25% by mass or less, and further preferably 5% by mass or more and 20% by mass or less, relative to the total mass of the (meth)acrylic acid-based copolymer A.
[0128] In order to adjust the solubility and viscosity index in the base oil, the (meth)acrylic acid copolymer A may further contain a structural unit derived from other vinyl radical polymerizable monomers in addition to the methacrylate alkyl ester a1, the acrylate alkyl ester a2, the acrylate alkyl ester a3, and the (meth)acrylate alkoxyalkyl ester a4.
[0129] Examples of other vinyl radical polymerizable monomers include vinyl compounds such as styrene and vinyl acetate; (meth)acrylic acid esters containing a carboxyl group such as (meth)acrylic acid, 2-(meth)acryloxyethyl succinate, 2-(meth)acryloxyethyl maleate, 2-(meth)acryloxyethyl phthalate, and 2-(meth)acryloxyethyl hexahydrophthalate; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, and tert-butyl methacrylate. , alkyl methacrylates having 1 to 4 carbon atoms, such as sec-butyl methacrylate; alkyl (meth)acrylates having 15 or more carbon atoms in the alkyl group, such as hexadecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerol mono(meth)acrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, etc. (Meth)acrylates having a hydroxyl group such as acrylates; phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, (1-naphthyl)methyl (meth)acrylate (meth)acrylates with aromatic ring structures, such as (meth)acrylate tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, (meth)acryloylmorpholine, etc.; (meth)acrylate heterocyclic structures, such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, (meth)acrylamide, etc. These can also be used in combination of two or more.
[0130] The above-mentioned (meth)acrylic copolymer A may be a block copolymer, a random copolymer, or a graft copolymer. Since the viscosity index can be improved by including a plurality of structural units having different solubility with respect to the base oil, a graft copolymer is preferred. The above-mentioned graft copolymer preferably includes structural units derived from a vinyl-based free radical polymerizable monomer m1 and structural units derived from a macromonomer M other than the above-mentioned m1. It should be noted that two or more macromonomers M may also be used in combination. As a branch component of the above-mentioned graft copolymer, it is preferred to include structural units derived from the macromonomer M. As a main component of the above-mentioned graft copolymer, it is preferred to include structural units derived from the monomer m1 described later.
[0131] Examples of the monomer m1 include styrene, vinyl acetate, and (meth)acrylate compounds. Examples of the (meth)acrylate compounds include the methacrylate alkyl ester a1, the acrylate alkyl ester a2, and the acrylate alkyl ester a3.
[0132] Examples of other (meth)acrylate compounds include (meth)acrylic acid, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, and other carboxyl group-containing (meth)acrylates; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, sec-butyl methacrylate, and other methacrylic acid alkyls having 1 to 4 carbon atoms; esters; alkyl (meth)acrylates having an alkyl group with 15 or more carbon atoms, such as hexadecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerol mono(meth)acrylate, ethylene glycol mono(meth)acrylate, and propylene glycol mono(meth)acrylate; phenyl (meth)acrylate, (Meth)acrylates having an aromatic ring structure, such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate, (1-naphthyl)methyl (meth)acrylate; tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate , (meth)acrylates with heterocyclic structures such as (meth)acryloylmorpholine; (meth)acrylate alkoxy esters such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate; 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, (meth)acrylamide, etc. They can also be used in combination of two or more.
[0133] It should be noted that the above-mentioned alkyl methacrylate a1, the above-mentioned alkyl acrylate a2 and the above-mentioned alkyl acrylate a3 may be contained in any one of the above-mentioned monomer m1 and the macromonomer M, or in both of them. However, from the perspective of easy adjustment of solubility in the base oil, the above-mentioned vinyl-based free radical polymerizable monomer m1 is preferably the above-mentioned alkyl acrylate a2 and the above-mentioned alkyl acrylate a3.
[0134] In addition, the macromonomer M is not particularly limited as long as it is a polymer having a free radical polymerizable group, but from the perspective of high solubility in base oil, it is preferably a compound containing two or more structural units derived from a monomer m2 having a vinyl free radical polymerizable group and having a free radical polymerizable group at the end. As the monomer m2, the same monomers as the vinyl free radical polymerizable monomers listed as the monomer m1 can be cited. From the perspective of excellent viscosity index improvement effect, the monomer m2 preferably contains an alkyl methacrylate having an alkyl group with 5 or more carbon atoms, and from the perspective of excellent solubility in base oil, it is further preferably contained in the alkyl methacrylate a1.
[0135] Furthermore, the macromonomer M is preferably a structure represented by the following formula 2 from the viewpoint of radical polymerizability with the monomer m1.
[0136] [Chemistry 2]
[0137]
[0138] (Where X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH. 1 ~Y n is a substituent bonded to the vinyl group of the component (m2) as a monomer structural unit, for example, OR 1 , halogen atoms, COR 2 、COOR 3 、CN、CONR 4 R 5 、NHCOR 6 , or R 7 , R 1 ~R 7 Each independently represents a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, a cyclic ether group, a heteroaryl group, etc. Z represents a terminal group, and n represents an integer of 2 to 10000. It should be noted that Z of the terminal group can be a hydrogen atom and a group derived from a free radical polymerization initiator, similarly to the terminal group of a polymer obtained by known free radical polymerization.
[0139] The number average molecular weight of the macromonomer M as measured by gel permeation chromatography is preferably 500 to 30,000, more preferably 1,000 to 25,000, and particularly preferably 2,000 to 20,000, from the viewpoint of improving the solubility in the base oil and the viscosity index.
[0140] The macromonomer M may be a monomer produced by a known method or a commercially available monomer. Examples of the method for producing the macromonomer M include a method using a cobalt chain transfer agent (U.S. Patent No. 4,680,352), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (International Publication No. 88 / 04304), a method of chemically bonding a polymerizable group (Japanese Patent Application Publication No. 60-133007 and U.S. Patent No. 5,147,952), and a method utilizing thermal decomposition (Japanese Patent Application Publication No. 11-240854).
[0141] The method using a cobalt chain transfer agent is preferred because the number of production steps is small and a catalyst with a high chain transfer constant is used. Since the cobalt chain transfer agent has a high chain transfer constant, a macromonomer with a controlled molecular weight can be obtained by adding a small amount of the cobalt chain transfer agent.
[0142] As the cobalt chain transfer agent, a known cobalt complex can be used. The amount of the cobalt chain transfer agent is preferably 0.00001 to 0.1 parts by mass, more preferably 0.00005 to 0.05 parts by mass, and particularly preferably 0.0001 to 0.02 parts by mass, relative to 100 parts by mass of the vinyl radical polymerizable monomer m2.
[0143] The total light transmittance of the polymer composition of the present invention, when measured by the method described later in Examples, is preferably 85 to 95%, more preferably 88 to 93%, and even more preferably 90 to 93%.
[0144] When the polymer composition of the present invention is measured by the method described later in Examples, the viscosity index (VI) calculated by the method of JIS-K2283-1993 is preferably 200 to 300, more preferably 205 to 300, and even more preferably 210 to 300.
[0145] <Method for producing polymer composition>
[0146] Next, an example of a method for producing the polymer composition of the present invention is described.
[0147] The polymer composition of the present invention can be produced by polymerizing a monomer mixture containing a macromonomer and a vinyl radical polymerizable monomer other than the macromonomer in a base oil by a known method.
[0148] Next, another example of the method for producing the polymer composition of the present invention is shown.
[0149] The polymer composition of the present invention can be produced by polymerizing a monomer mixture containing the methacrylate a1, the acrylate a2, and the acrylate a3 in a base oil by a known method.
[0150] Examples of the base oil include mineral base oils refined from crude oil and synthetic oils synthesized by chemical synthesis. Examples of commercially available base oils include API Group III base oils such as YUBASE 3 manufactured by SK Lubricant Co., Ltd. and API Group III Plus base oils such as YUBASE 4 manufactured by SK Lubricant Co., Ltd.
[0151] In addition, the monomer mixture may include a macromonomer M. The macromonomer M is preferably a macromonomer obtained by polymerizing a monomer mixture including a vinyl radical polymerizable monomer in the base oil using a cobalt chain transfer agent. Since the cobalt chain transfer agent has a high chain transfer constant, a macromonomer with a controlled molecular weight can be obtained by adding a small amount of the cobalt chain transfer agent. In addition, the macromonomer preferably includes the methacrylate alkyl ester a1 as a structural unit.
[0152] Examples of the vinyl radical polymerizable monomer include the polymerizable monomer m1, and preferably include the alkyl acrylate a2 and the alkyl acrylate a3.
[0153] In the present invention, a mixture of polymers having different structures such as a diblock copolymer and a graft copolymer, that is, the polymer composition of the present invention, can be obtained by polymerizing a monomer mixture containing the above-mentioned macromonomer and a vinyl radical polymerizable monomer other than the above-mentioned macromonomer.
[0154] The polymerization may be carried out under known conditions, but it is preferred to use α-methylstyrene dimer as the chain transfer agent because of its particularly excellent effect of suppressing heat generation during polymerization.
[0155] <Lubricant additives>
[0156] The polymer composition containing the (meth)acrylic copolymer A of the present invention can be used as a lubricant additive added to lubricants such as motor oils, gear oils, and hydraulic oils used in mobility equipment such as industrial machinery, robots, and automobiles.
[0157] Examples of the base oils for the above-mentioned engine oils, gear oils, hydraulic oils, etc. include mineral base oils refined from crude oil and synthetic oils produced by chemical synthesis. Examples of commercially available base oils include base oils of API standard Group III such as YUBASE 3 manufactured by SK Lubricant Co., Ltd. and base oils of API standard Group III Plus such as YUBASE 4 manufactured by SK Lubricant Co., Ltd.
[0158] Examples of lubricating oil additives include antioxidants, viscosity index improvers, pour point depressants, detergent dispersants, corrosion inhibitors, rust inhibitors, extreme pressure agents, oiliness improvers, defoamers, emulsifiers, antiwear agents, friction modifiers, mildew inhibitors, and anti-emulsifiers.
[0159] <Viscosity index improver>
[0160] Furthermore, the polymer composition of the present invention can be used as a viscosity index improver for the above-mentioned lubricating oil.
[0161] The degree of increase in dynamic viscosity caused by the addition of a viscosity index improver is preferably greater at high temperatures and smaller at low temperatures. It is known that, in general, a viscosity index improver composed of a (meth)acrylate polymer does not completely dissolve at low temperatures and forms a fine particle structure, and as the temperature rises, the solubility increases, thereby extending the polymer chain and exhibiting the above-mentioned function. As a performance index of a viscosity index improver, a viscosity index calculated from the dynamic viscosity at low temperatures (e.g., 40°C) and high temperatures (e.g., 100°C) is used.
[0162] The viscosity index is a value measured by the method of JIS-K2283-1993. The larger the value, the smaller the viscosity change caused by temperature. In addition, in recent years, regarding viscosity index improvers, higher values have begun to be required for the viscosity under high temperature (150°C) and high shear conditions (HTHS 150°C viscosity), so it is preferred that it will not completely dissolve even at 100°C, and the viscosity improvement effect can be expected even at higher temperatures. The dissolved state at 100°C can be evaluated by, for example, small angle X-ray scattering measurement (SAXS).
[0163] <Lubricating oil composition>
[0164] The lubricating oil composition containing the polymer composition of the present invention may contain various additives in addition to the polymer composition of the present invention. Examples of other additives include antioxidants, viscosity index improvers, pour point depressants, detergent dispersants, corrosion inhibitors, rust inhibitors, extreme pressure agents, oiliness improvers, defoamers, emulsifiers, antiwear agents, friction modifiers, mildew inhibitors, and anti-emulsifiers.
[0165] The content of the polymer composition of the present invention contained in the lubricating oil composition is preferably 0.01 to 30% by mass, more preferably 0.05 to 25% by mass, and most preferably 0.1 to 20% by mass, when the total mass of the lubricating oil composition is 100% by mass. By setting the content of the polymer composition to 0.01% by mass or more, the viscosity index of the lubricating oil composition can be improved, and by setting the content to 30% by mass or less, the dynamic viscosity of the lubricating oil composition at low temperatures can be suppressed, thereby improving fuel efficiency.
[0166] Example
[0167] Hereinafter, the present invention will be described in further detail by way of Examples and Comparative Examples. It should be noted that "parts" in the Examples represent "parts by mass". Evaluation was performed by the following method.
[0168] <Molecular weight of polymer composition>
[0169] The determination was performed using gel permeation chromatography (GPC) (HLC-8320 manufactured by Tosoh Corporation). After preparing a 0.2% by mass tetrahydrofuran solution of the polymer composition, 10 μl of the solution was injected into a device equipped with two Tosoh columns (TSKgelSuperHZM-H (inner diameter 6.0 mm, length 15 cm), TSKguardcolumn SuperHZ-H (inner diameter 4.6 mm, length 3.5 cm)), and the flow rate was 0.5 ml / min, eluent: tetrahydrofuran (stabilizer BHT), column temperature: 40°C, and the mass average molecular weight (Mw), number average molecular weight (Mn), and peak molecular weight (Mp) were calculated by standard polystyrene conversion.
[0170] <Molecular weight of macromonomer M>
[0171] The measurement was performed using gel permeation chromatography (GPC) (HLC-8320 manufactured by Tosoh Corporation). A 0.2% by mass tetrahydrofuran solution of the macromonomer M was prepared, and 10 μl of the solution was injected into a device equipped with a chromatographic column manufactured by Tosoh Corporation (TSKgelSuperHZM-M (inner diameter 4.6 mm, length 15 cm), HZM-M (inner diameter 4.6 mm, length 15 cm), HZ-2000 (inner diameter 4.6 mm, length 15 cm), TSKguardcolumn SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm)), and the measurement was performed under the conditions of flow rate: 0.35 ml / min, eluent: tetrahydrofuran (stabilizer BHT), and column temperature: 40°C. The mass average molecular weight (Mw) and number average molecular weight (Mn) were calculated by conversion to standard polystyrene.
[0172] <Small angle X-ray scattering (SAXS)>
[0173] A base oil solution containing 35% by mass of the polymer composition obtained in Example was placed in Small-angle X-ray scattering measurement was performed at measurement temperatures of 25°C and 100°C in a quartz capillary.
[0174] Small-angle X-ray scattering measurement was performed using SAXSpoint2.0 system manufactured by Anton Paar. Regarding the small-angle X-ray scattering measurement conditions, Cu Kα (wavelength ), the exposure time was set to 30 min (10 min × 3 times), the measurement environment was set to vacuum, and the camera length was set to 570 mm.
[0175] A capillary sample of a base oil solution of a (meth)acrylic acid copolymer was irradiated with X-rays to obtain a one-dimensional scattering distribution. The same measurement as above was also carried out using a quartz capillary.
[0176] The background correction is performed based on the one-dimensional scattering distribution obtained by the above steps. Specifically, the one-dimensional scattering distribution of only the base oil is corrected for transmittance based on the one-dimensional scattering distribution of each sample and then subtracted to obtain a one-dimensional scattering distribution after background correction.
[0177] Next, according to Journal of Physics: Conference Series 247 (2010) 012005, an absolute scattering intensity correction of the one-dimensional scattering distribution is performed. Specifically, the glassy carbon used as a sample for absolute scattering intensity correction is subjected to small-angle X-ray scattering measurement under the same analytical conditions as above without being placed in a capillary tube to obtain the one-dimensional scattering distribution of the glassy carbon. Next, the one-dimensional scattering distribution in the state without placing a sample is corrected for transmittance based on the one-dimensional scattering distribution of the glassy carbon and subtracted to obtain the background-corrected one-dimensional scattering distribution of the glassy carbon. The background-corrected one-dimensional scattering distribution of the glassy carbon is divided by the thickness (cm) and the exposure time (S) to obtain the scattering distribution ST per unit thickness and per unit time.
[0178] Next, the differential scattering cross-sectional area of glassy carbon published by the National Institute of Standards and Technology (NIST) of the United States was prepared and divided by 0.1 nm. -1 ≤q≤1nm -1 The above scattering distribution ST at each q in the range is obtained to obtain the coefficient value at each q. The average value of the coefficient value is used as the proportional coefficient for calculating the differential scattering cross-sectional area. Next, the one-dimensional scattering distribution after background correction of the base oil solution of each polymer composition is divided by the diameter (cm) of the capillary and the exposure time (s), thereby correcting it to the scattering intensity per unit thickness and per unit time, and multiplying it by the proportional coefficient obtained by the above method to obtain the standardized backscattering intensity (differential scattering cross-sectional area (cm -1 )), and normalized backscatter distribution.
[0179] <Viscosity Index (VI)>
[0180] The evaluation was carried out using a fully automatic simple dynamic viscometer (manufactured by Cannon, trade name: Simple-VIS) according to ASTM D7279 (D445). The dynamic viscosity (Vk100) of the polymer composition obtained in this example at 100°C was 6.5 mm 2 The concentration was adjusted using YUBASE4 at a rate of 1:1 / s, and the dynamic viscosity (Vk40) of the polymer composition at 40°C was measured by further adjusting the concentration.
[0181] Using the obtained "Vk100" and "Vk40", the viscosity index (VI) was calculated according to the method of JIS-K2283-1993.
[0182] <Solubility in base oil>
[0183] A base oil solution containing 35% by mass of the polymer obtained in this example was sandwiched between two 1 mm thick flat glasses using a 2 mm thick silicone rubber as a gasket, and the total light transmittance was measured using a haze meter (trade name: HM-150, manufactured by Murakami Color Research Laboratory).
[0184] [Production Example 1]
[0185] (Synthesis of Co complex (cobalt chain transfer agent))
[0186] Under a nitrogen atmosphere, 2.00 g (8.03 mmol) of cobalt (II) acetate tetrahydrate (Wako Pure Chemical Industries, Ltd., Wako Special Grade), 3.86 g (16.1 mmol) of diphenylglyoxime (Tokyo Chemical Industry Co., Ltd., EP Grade) and 100 ml of diethyl ether previously deoxygenated by nitrogen bubbling were added to a synthesis apparatus equipped with a stirring device, and the mixture was stirred at 25°C for 2 hours.
[0187] Next, 20 ml of boron trifluoride diethyl ether complex (manufactured by Tokyo Chemical Industry Co., Ltd., EP grade) was added and stirred for further 6 hours. The obtained substance was filtered, the solid was washed with diethyl ether, and dried at 100 MPa or less and 20° C. for 12 hours to obtain 5.02 g (7.93 mmol, yield 99 mass %) of Co complex (1) as a dark brown solid.
[0188] [Production Example 2]
[0189] 50 parts of YUBASE4, 50 parts of ACRYESTERSL (manufactured by Mitsubishi Chemical Corporation, trade name: ACRYESTER SL, a mixture of alkyl methacrylate having 12 carbon atoms in the alkyl group and alkyl methacrylate having 13 carbon atoms in the alkyl group), and 0.0015 parts of the Co complex prepared in Production Example 1 were added to a reaction container equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen gas was blown in while stirring to remove dissolved oxygen. After the liquid temperature was raised to 85°C, a mixed solution consisting of ACRYESTER SL (50 parts) and 0.5 parts of 1,1,3,3-tetramethylbutyl peroxy 2-ethylhexanoate (manufactured by NOF Corporation, trade name: PEROCTAO) as a polymerization initiator was added dropwise over 4 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (35 parts) and PEROCTA O (0.4 parts) was added, and the temperature was raised to 95°C. The liquid temperature was maintained at 95° C. for 4 hours and then cooled to obtain a YUBASE4 solution containing 54% by mass of the macromonomer M1. Table 1 shows the results of GPC of the obtained macromonomer.
[0190] [Production Examples 3 to 5]
[0191] Macromonomers M2 to M4 were obtained in the same manner as in Production Example 2 except that the amount of the Co complex shown in Table 1 was changed.
[0192] [Production Example 6]
[0193] 40 parts of YUBASE4, 98 parts of ACRYESTERSL, 2 parts of methyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: ACRYESTER M), 0.003 parts of the Co complex prepared in Preparation Example 1, and 0.1 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PERBUTYL O) as a polymerization initiator were added to a reaction container equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in to remove dissolved oxygen while stirring. The liquid temperature was raised to 90°C and maintained at 90°C for 2.5 hours. Then, a mixed solution consisting of YUBASE4 (20 parts) and PERBUTYL O (0.7 parts) was dropped over 1 hour, and the liquid temperature was raised to 105°C. After being maintained at 105°C for 1 hour, YUBASE4 (30 parts) was added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M5. The results of GPC of the obtained macromonomer are shown in Table 1.
[0194] [Production Example 7]
[0195] 60 parts of YUBASE4, 98 parts of ACRYESTERSL, 2 parts of methyl methacrylate, 0.005 parts of the Co complex prepared in Preparation Example 1, and 0.1 parts of tert-amyl peroxy 2-ethylhexanoate (manufactured by Arkema Gifu Co., Ltd., trade name LUPEROX 575) as a polymerization initiator were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 90°C and maintained at 90°C for 2.5 hours. Then, a mixed solution consisting of YUBASE4 (10 parts) and PERBUTYL O (0.7 parts) was dripped in 1 hour, and the liquid temperature was raised to 105°C. After being kept at 105°C for 1 hour, YUBASE4 (20 parts) was further added and cooled to obtain a YUBASE4 solution containing 52.6% by mass of the macromonomer M6. The results of GPC of the obtained macromonomer are shown in Table 1.
[0196] <Example 1>
[0197] 78.7 parts of YUBASE4, 25 parts of ACRYESTER SL, 52 parts of n-butyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name: nBA), 23 parts of lauryl acrylate (manufactured by Osaka Organic Chemical Co., Ltd., trade name: LA), 0.03 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: PERBUTYL O) as a polymerization initiator, and 0.03 parts of α-methylstyrene dimer (manufactured by NOF Corporation, trade name: NOFMER MSD) as a chain transfer agent were added to a reaction container equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in to remove dissolved oxygen. The liquid temperature was raised to 85°C, and maintained at 85°C for 2 hours, and then a mixed liquid of YUBASE4 (40 parts) and PERBUTYL O (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67 parts) and PEROCTAO (0.5 parts) was added and the temperature was raised to 95°C. The liquid temperature was maintained at 95°C for 1 hour and then cooled to obtain a solution containing 35% by mass of a (meth)acrylic acid-based copolymer. The evaluation results of the obtained polymer composition are shown in Table 2.
[0198] <Example 2>
[0199] 38.2 parts of YUBASE3, 46.3 parts of YUBASE4 solution of macromonomer M1 obtained in Preparation Example 2, 52 parts of n-butyl acrylate, 23 parts of lauryl acrylate, 0.015 parts of PERBUTYL O as a polymerization initiator, and 0.04 parts of NOFMER MSD as a chain transfer agent were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in to remove dissolved oxygen while stirring. The liquid temperature was raised to 85°C, and maintained at 85°C for 2 hours, and then a mixed solution of YUBASE3 (42 parts) and PERBUTYL O (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution composed of YUBASE3 (67.5 parts) and PEROCTAO (0.5 parts) was added, and the temperature was raised to 95°C, and the liquid temperature was maintained at 95°C for 1 hour. After adding YUBASE3 (16.7 parts), the mixture was cooled to obtain a solution containing 35% by mass of a (meth)acrylic acid-based copolymer. Table 2 shows the evaluation results of the obtained polymer composition.
[0200] <Example 3>
[0201] 7.6 parts of YUBASE4, 46.3 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3, 52 parts of n-butyl acrylate, 23 parts of lauryl acrylate, 0.015 parts of PERBUTYL O as a polymerization initiator, and 0.03 parts of NOFMER MSD as a chain transfer agent were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after being maintained at 85°C for 2 hours, a mixed solution of YUBASE4 (42 parts) and PERBUTYL O (0.015 parts) was added dropwise over 2 hours. Furthermore, after being maintained at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67.5 parts) and PEROCTAO (0.5 parts) was added, and the temperature was raised to 95°C, and the liquid temperature was maintained at 95°C for 1 hour. After adding YUBASE4 (46.7 parts), the mixture was cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer composition. Table 2 shows the evaluation results of the obtained polymer compositions.
[0202] <Example 7>
[0203] 12.5 parts of YUBASE4, 37 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3, 56 parts of n-butyl acrylate, 24 parts of lauryl acrylate, 0.015 parts of PERBUTYL O as a polymerization initiator, and 0.04 parts of NOFMER MSD as a chain transfer agent were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after being maintained at 85°C for 2 hours, a mixed solution of YUBASE4 (42 parts) and PERBUTYL O (0.015 parts) was dripped over 2 hours. Furthermore, after being maintained at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67.5 parts) and PEROCTAO (0.5 parts) was added, and the temperature was raised to 95°C, and the liquid temperature was maintained at 95°C for 1 hour. After adding YUBASE4 (46.7 parts), the mixture was cooled to obtain a solution containing 35% by mass of a (meth)acrylic acid copolymer. Table 3 shows the evaluation results of the obtained polymer compositions.
[0204] <Example 8>
[0205] 74 parts of the YUBASE4 solution of the macromonomer M2 obtained in Preparation Example 3, 42 parts of n-butyl acrylate, 18 parts of lauryl acrylate, 0.015 parts of PERBUTYL O as a polymerization initiator, and 0.02 parts of NOFMER MSD as a chain transfer agent were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after being maintained at 85°C for 2 hours, a mixed solution of YUBASE4 (42 parts) and PERBUTYL O (0.015 parts) was dripped over 2 hours. Furthermore, after being maintained at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67.5 parts) and PEROCTAO (0.5 parts) was added, and the temperature was raised to 95°C, and the liquid temperature was maintained at 95°C for 1 hour. After adding YUBASE4 (42.2 parts), the mixture was cooled to obtain a solution containing 35% by mass of a (meth)acrylic copolymer. Table 3 shows the evaluation results of the obtained polymer compositions.
[0206] <Example 13>
[0207] 40 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M5 obtained in Preparation Example 6, 52 parts of n-butyl acrylate, 23 parts of lauryl acrylate, 0.03 parts of LUPEROX 575 as a polymerization initiator, and 0.03 parts of NOFMER MSD as a chain transfer agent were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in to remove dissolved oxygen while stirring. The liquid temperature was raised to 85°C, and maintained at 85°C for 3.5 hours, and then a mixed solution of YUBASE4 (42 parts) and LUPEROX 575 (0.015 parts) was added dropwise over 2 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (20 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1 hour, and then the liquid temperature was raised to 110°C, and the liquid temperature was maintained at 110°C for 1 hour. After adding YUBASE4 (61.1 parts), the mixture was cooled to obtain a YUBASE4 solution containing 35% by mass of the polymer composition. Table 4 shows the evaluation results of the obtained polymer composition.
[0208] <Example 14>
[0209] 6.9 parts of YUBASE4, 47.6 parts of the YUBASE4 solution of the macromonomer M6 obtained in Preparation Example 7, 52 parts of n-butyl acrylate, 23 parts of lauryl acrylate, 0.015 parts of PERBUTYL O as a polymerization initiator, and 0.01 parts of NOFMER MSD as a chain transfer agent were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and after being maintained at 85°C for 2 hours, a mixed solution of YUBASE4 (42 parts) and PERBUTYL O (0.015 parts) was added dropwise over 2 hours. Furthermore, after being maintained at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (67.5 parts) and PEROCTAO (0.5 parts) was added, and the temperature was raised to 95°C, and the liquid temperature was maintained at 95°C for 1 hour. After adding YUBASE4 (46.7 parts), the mixture was cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer composition. Table 4 shows the evaluation results of the obtained polymer compositions.
[0210] <Example 15>
[0211] 30 parts of YUBASE4 and 47.6 parts of the YUBASE4 solution of the macromonomer M6 obtained in Preparation Example 7 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of YUBASE4 (25 parts), n-butyl acrylate (52 parts), lauryl acrylate (23 parts), and LUPEROX575 (0.1 parts) as a polymerization initiator was dripped over 4 hours. Further, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (50 parts) and LUPEROX 575 (0.5 parts) was dripped over 1.5 hours, and the liquid temperature was raised to 110°C. After maintaining at 110°C for 1 hour, YUBASE4 (58.1 parts) was added and cooled to obtain a YUBASE4 solution containing 35% by mass of a polymer composition. The evaluation results of the obtained polymer composition are shown in Table 4.
[0212] <Example 16>
[0213] 20 parts of YUBASE4 and 46.3 parts of the YUBASE4 solution of the macromonomer M3 obtained in Preparation Example 4 were added to a reaction vessel equipped with a stirrer, a cooling tube, and a thermometer, and nitrogen was blown in while stirring to remove dissolved oxygen. The liquid temperature was raised to 85°C, and a mixed solution consisting of YUBASE4 (25 parts), n-butyl acrylate (30 parts), lauryl acrylate (35 parts), 2-methoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name: 2-MTA) (10 parts), and LUPEROX 575 (0.1 parts) as a polymerization initiator was added dropwise over 4 hours. Furthermore, after maintaining at 85°C for 1 hour, a mixed solution consisting of YUBASE4 (60 parts) and LUPEROX 575 (0.5 parts) was added dropwise over 1.5 hours, and the liquid temperature was raised to 110°C. After maintaining at 110° C. for 1 hour, YUBASE 4 (59.4 parts) was added and then cooled to obtain a YUBASE 4 solution containing 35% by mass of the polymer composition. Table 4 shows the evaluation results of the obtained polymer composition.
[0214] <Examples 4 to 6, 9 to 12 and Comparative Example 1>
[0215] A polymer composition was obtained in the same manner as in Example 3 except that the type of macromonomer used, the type and amount of monomers, and the amount of α-methylstyrene dimer were changed to the contents of Tables 2 to 5. The evaluation results of the obtained polymer composition are shown in Tables 2 to 5.
[0216] <Examples 17 and 18>
[0217] A polymer composition was obtained in the same manner as in Example 16 except that the type of macromonomer used, the type and amount of monomers used were changed to those shown in Table 4. Table 4 shows the evaluation results of the obtained polymer composition.
[0218] <Comparative Examples 2 to 6>
[0219] A polymer composition was obtained in the same manner as in Example 1 except that the types and amounts of the monomers used and the amount of α-methylstyrene dimer were changed as shown in Table 5. Table 5 shows the evaluation results of the obtained polymer composition.
[0220] In Comparative Examples 1 to 5, the viscosity index was reduced.
[0221] [Table 1]
[0222]
[0223] [Table 2]
[0224]
[0225] [Table 3]
[0226]
[0227] [Table 4]
[0228]
[0229] [Table 5]
[0230]
[0231] The abbreviations in Tables 1 to 5 are as follows.
[0232] SLMA: A mixture of an alkyl methacrylate having an alkyl group with 12 carbon atoms and an alkyl methacrylate having an alkyl group with 13 carbon atoms (manufactured by Mitsubishi Chemical Corporation, trade name: ACRYESTER SL)
[0233] ·MMA: Methyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: ACRYESTER M)
[0234] EHA: 2-ethylhexyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name: 2-ethylhexyl acrylate)
[0235] Co complex: the cobalt chain transfer agent obtained in Production Example 1.
[0236] α-Methylstyrene dimer (manufactured by NOF Corporation, trade name: NOFMER MSD)
[0237] YUBASE3 (API standard Group III base oil, manufactured by SK Lubricants Co., Ltd.)
[0238] YUBASE4 (API standard Group III Plus base oil, manufactured by SK Lubricants Co., Ltd.)
[0239] LA: Lauryl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name: LA)
[0240] BA: n-butyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name: butyl acrylate)
[0241] EA: Ethyl acrylate (manufactured by Mitsubishi Chemical Corporation, trade name: ethyl acrylate)
[0242] · BMA: n-butyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: ACRYESTER B)
[0243] ·2-MTA: 2-methoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name: 2-MTA)
[0244] Industrial Applicability
[0245] According to the present invention, a polymer composition, a viscosity index improver, and a lubricating oil composition having a high viscosity index improving effect can be provided.
[0246] Furthermore, according to the method for producing a polymer composition of the present invention, a polymer composition having a high viscosity index improvement effect can be produced.
[0247] Furthermore, according to the method for producing a macromonomer of the present invention, it is possible to produce a macromonomer capable of producing a polymer composition having a high viscosity index-improving effect.
Claims
1. A polymer composition, comprising a (meth)acrylic copolymer A, The (meth)acrylic copolymer A is a copolymer comprising a structural unit derived from a methacrylic acid alkyl ester a1 having an alkyl group with 5 to 14 carbon atoms, a structural unit derived from an acrylate alkyl ester a2 having an alkyl group with 5 to 14 carbon atoms, and a structural unit derived from an acrylate alkyl ester a3 having an alkyl group with 1 to 4 carbon atoms, The (meth)acrylic copolymer A is a graft copolymer, and the graft copolymer includes a structural unit derived from a vinyl radical polymerizable monomer m1 and a structural unit derived from a macromonomer M other than the vinyl radical polymerizable monomer m1. The vinyl free radical polymerizable monomer m1 is an alkyl acrylate a2 having an alkyl group with 5 to 14 carbon atoms and an alkyl acrylate a3 having an alkyl group with 1 to 4 carbon atoms. The macromonomer M includes a structural unit derived from a vinyl radical polymerizable monomer m2, wherein the vinyl radical polymerizable monomer m2 includes an alkyl methacrylate a1 having an alkyl group with 5 to 14 carbon atoms, The differential distribution value in the differential molecular weight distribution curve of the polymer composition measured by gel permeation chromatography satisfies the following formula 1, The size q of the scattering vector of a 35 wt% base oil solution of the polymer composition at 25° C. in small-angle X-ray scattering is 0.07 nm -1 Above and 2nm -1 The maximum value of the normalized backscatter intensity within the range below 40 cm -1 above, dMp30 / dMp≥0.65…1 dMp30: The differential distribution value of the molecular weight corresponding to 30% of the peak molecular weight measured by gel permeation chromatography, dMp: differential distribution value of peak top molecular weight measured by gel permeation chromatography, Base oil: API standard Group III, or Group III Plus. 2 . The polymer composition according to claim 1 , wherein the (meth)acrylic copolymer A comprises 1 to 50% by mass of a structural unit derived from the alkyl methacrylate a1 based on the total mass of the (meth)acrylic copolymer A. 3 .
3. A polymer composition comprising a (meth)acrylic copolymer A, The (meth)acrylic copolymer A is a copolymer comprising a structural unit derived from a methacrylic acid alkyl ester a1 having an alkyl group with 5 to 14 carbon atoms, a structural unit derived from an acrylate alkyl ester a2 having an alkyl group with 5 to 14 carbon atoms, and a structural unit derived from an acrylate alkyl ester a3 having an alkyl group with 1 to 4 carbon atoms, The (meth)acrylic copolymer A is a graft copolymer, and the graft copolymer includes a structural unit derived from a vinyl radical polymerizable monomer m1 and a structural unit derived from a macromonomer M other than the vinyl radical polymerizable monomer m1. The vinyl free radical polymerizable monomer m1 is an alkyl acrylate a2 having an alkyl group with 5 to 14 carbon atoms and an alkyl acrylate a3 having an alkyl group with 1 to 4 carbon atoms. The macromonomer M includes a structural unit derived from a vinyl radical polymerizable monomer m2, wherein the vinyl radical polymerizable monomer m2 includes an alkyl methacrylate a1 having an alkyl group with 5 to 14 carbon atoms, The (meth)acrylic copolymer A includes 1 to 50% by mass of a structural unit derived from the alkyl methacrylate a1, based on the total mass of the (meth)acrylic copolymer A. 4 . The polymer composition according to claim 1 , wherein the (meth)acrylic copolymer A comprises 1 to 50% by mass of a structural unit derived from the alkyl acrylate a2 based on the total mass of the (meth)acrylic copolymer A. 5 . 5 . The polymer composition according to claim 1 , wherein the (meth)acrylic copolymer A comprises 30 to 80% by mass of a structural unit derived from the alkyl acrylate a3 based on the total mass of the (meth)acrylic copolymer A.
6. A polymer composition comprising a (meth)acrylic copolymer A, The (meth)acrylic copolymer A is a copolymer comprising a structural unit derived from a methacrylic acid alkyl ester a1 having an alkyl group with 5 to 14 carbon atoms, a structural unit derived from an acrylate alkyl ester a2 having an alkyl group with 5 to 14 carbon atoms, and a structural unit derived from an acrylate alkyl ester a3 having an alkyl group with 1 to 4 carbon atoms, The (meth)acrylic copolymer A is a graft copolymer, and the graft copolymer includes a structural unit derived from a vinyl radical polymerizable monomer m1 and a structural unit derived from a macromonomer M other than the vinyl radical polymerizable monomer m1. The vinyl free radical polymerizable monomer m1 is an alkyl acrylate a2 having an alkyl group with 5 to 14 carbon atoms and an alkyl acrylate a3 having an alkyl group with 1 to 4 carbon atoms. The macromonomer M includes a structural unit derived from a vinyl radical polymerizable monomer m2, wherein the vinyl radical polymerizable monomer m2 includes an alkyl methacrylate a1 having an alkyl group with 5 to 14 carbon atoms, The (meth)acrylic copolymer A contains 30 to 80% by mass of a structural unit derived from the alkyl acrylate a3 based on the total mass of the (meth)acrylic copolymer A. 7 . The polymer composition according to claim 6 , wherein the (meth)acrylic copolymer A comprises 1 to 50% by mass of a structural unit derived from the alkyl acrylate a2 based on the total mass of the (meth)acrylic copolymer A. 8 . 8 . The polymer composition according to claim 1 , wherein the (meth)acrylic copolymer A is a copolymer comprising a structural unit derived from an alkoxyalkyl (meth)acrylate a4. 9 . The polymer composition according to claim 8 , wherein the (meth)acrylic copolymer A comprises 1 to 30% by mass of a structural unit derived from the alkoxyalkyl (meth)acrylate a4 based on the total mass of the (meth)acrylic copolymer A.
10. The polymer composition according to claim 3 or 6, wherein the differential distribution value in the differential molecular weight distribution curve measured by gel permeation chromatography satisfies the following formula 1: dMp30 / dMp≥0.65…1 dMp30: The differential distribution value of the molecular weight corresponding to 30% of the peak molecular weight. dMp: differential distribution value of peak top molecular weight.
11. The polymer composition according to claim 1, 3 or 6, wherein the scattering vector size q of a 35 wt% base oil solution of the polymer composition in API standard Group III or Group III Plus at 100°C is 0.1 nm -1 The normalized backscatter intensity at 1 cm -1 above.
12. The polymer composition according to claim 1, 3 or 6, wherein the mass average molecular weight of the polymer composition measured by gel permeation chromatography is 50,000 to 2,000,000. 13 . The polymer composition according to claim 1 , 3 or 6 , which has a molecular weight distribution of 5 to 20 as measured by gel permeation chromatography.
14. The polymer composition according to claim 1, 3 or 6, wherein the macromonomer M has a structure of the following formula 2, [Chemistry 1] Where, X 1 ~X n-1 Each independently represents a hydrogen atom, a methyl group or CH2OH, Y 1 ~Y n Each independently represents a substituent bonded to the vinyl group of the vinyl radical polymerizable monomer m2, Z represents a terminal group, and n represents an integer of 2 to 10,000. 15 . The polymer composition according to claim 1 , 3 or 6 , wherein the number average molecular weight of the macromonomer M measured by gel permeation chromatography is 500 to 30,000.
16. A lubricating oil additive comprising the polymer composition according to any one of claims 1 to 15.
17. A viscosity index improver comprising the polymer composition of any one of claims 1 to 15.
18. A lubricating oil composition comprising the polymer composition according to any one of claims 1 to 15.
19. The method for producing a polymer composition according to any one of claims 1 to 15, which is a method for producing a polymer composition comprising polymerizing a monomer mixture containing a macromonomer and a vinyl radical polymerizable monomer in a base oil, The macromonomer is a macromonomer polymerized in a base oil. 20 . The method for producing a polymer composition according to claim 19 , wherein α-methylstyrene dimer is used as a chain transfer agent.
21. A lubricating oil composition comprising the polymer composition according to claim 14 or 15 and a base oil.
